The revision of the restrictive lists of medicinal products - B. K. Romanov; Yu. V. Olefir; V. A. Merkulov; Y. O. Pegova (Безопасность и риск фармакотерапии)
Information about the new rules and the outcome of the revision of the four restrictive lists of medicaments are submitted. Lists of vital and essential medicines, «preferential» list of drugs prescribed by a decision of medical commissions, the list of expensive drugs and the list of drugs constituting minimum pharmaceutical assortment are important documents for the pharmaceutical industry and for society as a whole, since the prices of drugs included in these lists are regulated by goverment. The problems of restrictive lists preparation are indicated. The recommendations for further improvement of the system of preparation of restrictive lists of medicaments are given.